EDUKASI DAN EKSPLORASI PENGOLAHAN KOPI DI PERHUTANAN SOSIAL DESA JAMBEWANGI, KABUPATEN BANYUWANGI - Muhammad Agung Zaim Adzkiya; Medhanita Dewi Renanti; Soni Trison (Universitas Mataram, 2023)
Indonesia is known as a coffee producer in the world, with no less than 300,000 tons of coffee beans being exported abroad, both Arabica and Robusta types. Most of the coffee plants are planted and cultivated around the forest. Mitra Hutan Lestari is a Forest Village Community Institution located in Jambewangi Village, Sempu District, Banyuwangi Regency with an area of lap forest of not less than 7000 hectares, and one of the commodities that has not been utilized optimally is coffee. The purpose of this community service program is to educate and explore coffee processing in social forestry. Community Institutions Forest Village Partners Sustainable Forests in Banyuwangi Regency. The approach employed in education is the provision of equipment for processing coffee, from coffee's harvest till it is served. Investigation of coffee plant varieties is done by visiting social forestry sites and identifying the varieties of coffee plants in forested areas. For all training participants, the pre-test and post-test procedures were used to evaluate the training. The general description of participants in the education and exploration training on coffee processing was that they liked coffee drinks with a bitter taste for the male participants, and female participants preferred coffee drinks with a combination of milk and syrup with various flavors. The results of the pre-test and post-test analysis showed that there was an increase in participants' knowledge, starting from the procedures for harvesting coffee cherries, processing coffee cherries into coffee beans, assessing the value of defects in coffee beans, and roasting and brewing coffee. Training participants through exploration activities has enabled them to distinguish the types of coffee that exist in social forestry areas. It has been possible to increase the knowledge and enthusiasm of the training participants to develop coffee in the social forestry area thanks to the existence of educational training and exploration of coffee processing.